Physical-chemical and sensory evaluation of bread made with forage palm flour (Opuntia ficus-indica) (Research, Society and Development, 2021)
The study evaluated the physicochemical and sensory characteristics of loaf Bread with the addition of 0%(FP0), 5%(FP5), 10%(FP10) and 15%(FP15) of forage palm flour, replacing the flour of white wheat. The breads were subjected to sensory analysis by 106(one hundred and six) untrained judges. The FP5 bread was the most accepted, with na acceptability rate of 75%. Analyzes of total phenolic compounds and antioxidant activity were performed by the ABTS•⁺ radical capture method, in FP0 and FP5, however, the analyzed samples did not show statistically significant difference between them by the Tukey test (p